Karakteristik Penderita Penyakit Jantung Bawaan Pada Anak di RSUD Doris Sylvanus - Trisia, Adelgrit; Anhar, Khansa Hanifah; Jafar, Muhammad; Gultom, Miranda (Barigas: Jurnal Riset Mahasiswa, 2025)
Congenital heart disease (CHD) is a structural abnormality of the heart from birth which causes morbidity, maternal, fetal and neonatal deaths throughout the world. Characteristics of the causes of congenital heart disease show geographic variations in the incidence of CHD. The aim of this study was to determine the variation in characteristics of pediatric CHD sufferers at Doris Sylvanus Regional Hospital. The type of research used is descriptive research with a retrospective approach by looking at the characteristics of children with CHD in medical record data. The sample for this study was 41 pediatric patients suffering from congenital heart disease at Doris Sylvanus Regional Hospital from January 2022-April 2024. The majority of respondents were > 2 years old, 15 (36.6%) and 21 (51.2%) men. the majority of VSDs were 17 (41.5%), the majority of clinical symptoms were bronchopneumonia, there were 11 (26.8%), the majority of comorbidities were failure to thrive, there were 8 (24.2%), the nutritional status of the majority was malnutrition, there were 27 (81.8% ) and the majority of Hb levels were 8.01-13 g/dL, there were 29 (70.7%). > 2 years, diagnosis of VSD, shortness of breath, failure to thrive, malnutrition, Hb 8.01-13 g/dL are risk characteristics for congenital heart disease in children at RSUD January 2022-April 2024. The conclusion is that the majority of children suffering from PJB are > 2 years old, the gender of the children suffering from PJB is male 51.2%, the diagnosis of VSD is 41.5%, clinical symptoms of shortness of breath are 51.2%, concomitant diseases of bronchopneumonia are 26.8%, nutritional status is poor as much as 75.6%, Hb levels are 8.01-13 g/dL as much as 70.7%.